2016
DOI: 10.1080/19336896.2016.1166324
|View full text |Cite
|
Sign up to set email alerts
|

A transfectant RK13 cell line permissive to classical caprine scrapie prion propagation

Abstract: ABSTRACT. To assess scrapie infectivity associated with caprine-origin tissues, bioassay can be performed using kids, lambs or transgenic mice expressing caprine or ovine prion (PRNP) alleles, but the incubation periods are fairly long. Although several classical ovine scrapie prion permissive cell lines with the ability to detect brain-derived scrapie prion have been available, no classical caprine scrapie permissive cell line is currently available. Therefore, the aims of this study were to generate a rabbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Potentially, prion protein could have a similar interaction with FN1. Additional studies of FN1 are warranted to determine if similar correlations with prion permissibility exist in other cell culture systems (i.e., Rov or cpRK13 [35]) and prion strains (i.e., natural scrapie isolates X124 or SSBP-1, Nor98, human prion isolates). Furthermore, future studies to silence FN1 or deletion of FN1 from culture media in order to create cell culture models for human prions may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, prion protein could have a similar interaction with FN1. Additional studies of FN1 are warranted to determine if similar correlations with prion permissibility exist in other cell culture systems (i.e., Rov or cpRK13 [35]) and prion strains (i.e., natural scrapie isolates X124 or SSBP-1, Nor98, human prion isolates). Furthermore, future studies to silence FN1 or deletion of FN1 from culture media in order to create cell culture models for human prions may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Dassanayake et al, demonstrated that RK13 cells engineered to express caprine PrP with haplotype 2 (cpRK13 cells) could be infected with natural caprine scrapie of haplotype 1,1 or haplotype 1,2, but not to natural cases with haplotypes 3 or 4. However, Tg338 mice, which express caprine scrapie with haplotype 2, were able to propagate these natural haplotype 3 and 4 isolates [ 56 ]. Therefore, these mice might possess specific cofactors necessary for propagation that are lacking in RK13 cells.…”
Section: Immortalized Cell Linesmentioning
confidence: 99%
“…Therefore, these mice might possess specific cofactors necessary for propagation that are lacking in RK13 cells. Subsequently, they found that after 2 serial passages of haplotype 3 or 4 scrapie isolates in Tg338 mice, cpRK13 cells were able to propagate these mouse-adapted isolates [ 56 ].…”
Section: Immortalized Cell Linesmentioning
confidence: 99%
“…RK13 cells were one of the first cell lines to replicate non-murineadapted prion strains, and the first to replicate natural ovine scrapie (Vilette et al, 2001). RK13 cells have proven to be an impressively versatile cell line given that they have been shown thus far to replicate ovine scrapie, caprine scrapie, vole-adapted BSE, CWD, and mouse prions upon expression of the appropriate PrP C molecule (Bian et al, 2010;Courageot et al, 2008;Dassanayake et al, 2016;Grassmann, Wolf, Hofmann, Graham, & Vorberg, 2013;Vilette et al, 2001). This versatility not only allows for the study of each prion disease individually but also offers researchers the ability to compare and study vari- Studying scrapie-infected MovS, in particular, may allow for greater insight into the processes by which prions invade the peripheral nervous system (Bedecs, 2008 (Archer et al, 2004;Neale et al, 2010;Sabuncu et al, 2003;Vilette et al, 2001).…”
Section: Ovine Scrapie Cell Linesmentioning
confidence: 99%
“…One cell line, RK13 cells transfected with caprine PrP C (cpRK13), has been reported to successfully and stably replicate goat scrapie prions (Dassanayake et al, 2016). Although a caprine scrapie-infected cell line derived from goat tissue would better mirror real-life conditions, previous attempts to establish such a model have failed (Oelschlegel et al, 2015).…”
Section: Caprine Scrapie Cell Linesmentioning
confidence: 99%